The Impact of Covid-19 on Online Learning Motivation in Sports Massage Learning - Komang Ayu Tri Widhiyanti; Ni Wayan Ary Rusitayanti; Ni Wayan Ariawati (STKIP Muhammadiyah Kuningan, 2022)
This study aims to determine the impact of the COVID-19 pandemic on online learning motivation, specifically for sports massage courses. The research design used in this study was Posttest Only Control Group Design. The samples were all students of the sixth semester of the Physical Education and Health Study Program, Universitas PGRI Mahadewa Indonesia, totaling 71 people. Research results in supporting an exciting learning process during a pandemic are highly demanded (1) lecturer skills in learning and developing knowledge that makes learning enjoyable, (2) student motivation in participating in learning is the key to success in the massage learning process, (3) supporting facilities online learning is the following key in the learning process during. The conclusion of this research is in carrying out learning practices and using engaging learning media that can provoke students' enthusiasm in the implementation of learning.